Protection of Intellectual Property Rights in the Field of Television and the Internet. The Notion of Teleformat - Ulianova Halyna; Nataliia Baadzhy; Oleksii Podoliev; Denys Vlasiuk; Hanna Chumachenko (Ius Humani. Jornal do direito, 2021)
The article is devoted to the main issues of protection of intellectual property rights in the field of television and the internet, related to the spread of piracy in the field of copyright and related rights, and to the unlicensed copying of television broadcasts. Moreover, there is an emphasis on the exacerbation of existing problems in the context of the Covid-19 pandemic and how this affected the industry. This research considers international and national legislation in the field of intellectual law, international experience of various countries, approaches to theory, and problems of implementing existing measures, in order to propose some options for optimizing existing mechanisms. The research methodology use the following methods: formal-legal, historical-legal, comparative analysis, and modeling. The main issues under consideration are the following ones: international broadcasting regulation, the problem of uniform terminology, and prospects for the legal regulation of copyright in television broadcasting. The authors defend the uncompromising protection of intellectual property, highlighting the lack of basic definitions, to propose their own definitions, in order to avoid the weak copyright protection of television broadcasting organizations.